1992
DOI: 10.1002/j.1460-2075.1992.tb05449.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans regulation in the Ultrabithorax gene of Drosophila: alterations in the promoter enhance transvection.

Abstract: We report a genetic and molecular study of UbxMX6 and Ubxl9Slxl, two We speculate that the region altered in the mutations may have a wildtype function to ensure cis-autonomy of the regulation of Ubx transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 50 publications
(81 reference statements)
4
37
0
Order By: Relevance
“…Prior genetic analyses have shown that, for many genes, enhancer action in trans is reduced in the presence of a promoter in cis (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008). Our data are consistent with the model that this reduction results from an enhancer sharing its activity between the two promoters.…”
Section: Cis-and Trans-promoters Compete For Enhancer Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…Prior genetic analyses have shown that, for many genes, enhancer action in trans is reduced in the presence of a promoter in cis (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008). Our data are consistent with the model that this reduction results from an enhancer sharing its activity between the two promoters.…”
Section: Cis-and Trans-promoters Compete For Enhancer Activitysupporting
confidence: 90%
“…Finally, in light of the extensive pairing in the Drosophila genome, how does an enhancer choose a target promoter when simultaneously presented with promoters in cis and in trans? For several genes, the presence of a promoter in cis reduces the strength of enhancer action in trans (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008), suggesting that promoters in cis and in trans compete for an enhancer's activity. Because these observations have been largely based on mutant phenotypes in whole animals, the cellular basis for this competition is not yet clear.…”
mentioning
confidence: 99%
“…Thus far, transvection has been observed at all genomic insertion sites tested, suggesting that the Drosophila genome is generally permissive to enhancer action in trans. Furthermore, transgenic experiments have demonstrated that promoters at allelic positions in cis and trans to an enhancer will compete for the enhancer's activity, consistent with earlier classical observations (Geyer et al 1990;Martinez-Laborda et al 1992;Casares et al 1997;Morris et al 1999;Gohl et al 2008). However, enhancer activation of promoters in cis and trans are not equivalent, with enhancers showing a strong preference for a promoter in cis, and frequently showing cell-to-cell variability in the activation of a promoter in trans (Bateman et al 2012a;Mellert and Truman 2012).…”
supporting
confidence: 83%
“…Thus, it is conceivable that enhancers that were scored negatively for transvection in the previous study were, in fact, restricted from acting in trans at detectable levels due to competition from the promoter in cis, whereas other enhancers in the study may have been less sensitive to the promoter in cis. Consistent with this hypothesis, the enhancers of the yellow gene do not appear to act in trans in the presence of a strong promoter in cis (Geyer et al 1990;Morris et al 1999), whereas enhancers from other genes will show low levels of transvection when juxtaposed to a strong cis-promoter and higher levels of transvection in the absence of a cis-promoter (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008;Bateman et al 2012a;Mellert and Truman 2012). We also found that two enhancers from our study differed in sensitivity to a promoter in cis, as Cre/loxP removal of the LTL promoter increased transvection by the klu enhancer but not by the pax enhancer.…”
Section: Discussionmentioning
confidence: 79%
“…Assuming that there are physical constraints on this process within the chromosome, this model predicts that an enhancer would preferentially activate a promoter located on the same DNA molecule (in cis) even if a potential target promoter is located on a paired homologous chromosome (in trans). Indeed, transvection in Drosophila displays just such a cis preference for a functional promoter (9)(10)(11)(12)(13). Recent experiments indicating that enhancer-proximal genes within a gene cluster are preferentially activated by a distant enhancer, unless their promoters are masked by repressive chromatin structures (14)(15)(16), are also consistent with a tracking mechanism.…”
mentioning
confidence: 99%